Biomimetic Alginate/Gelatin Cross-Linked Hydrogels Supplemented with Polyphosphate for Wound Healing Applications - Shunfeng Wang; Xiaohong Wang; Meik Neufurth; Emad Tolba; Hadrian Schepler; Shichu Xiao; Heinz C. Schröder; Werner E. G. Müller (Molecules, 2020)
In the present study, the fabrication of a biomimetic wound dressing that mimics the extracellular matrix, consisting of a hydrogel matrix composed of non-oxidized and periodate-oxidized marine alginate, was prepared to which gelatin was bound via Schiff base formation. Into this alginate/oxidized-alginate-gelatin hydrogel, polyP was stably but reversibly integrated by ionic cross-linking with Zn2+ ions. Thereby, a soft hybrid material is obtained, consisting of a more rigid alginate scaffold and porous structures formed by the oxidized-alginate-gelatin hydrogel with ionically cross-linked polyP. Two forms of the Zn-polyP-containing matrices were obtained based on the property of polyP to form, at neutral pH, a coacervate—the physiologically active form of the polymer. At alkaline conditions (pH 10), it will form nanoparticles, acting as a depot that is converted at pH 7 into the coacervate phase. Both polyP-containing hydrogels were biologically active and significantly enhanced cell growth/viability and attachment/spreading of human epidermal keratinocytes compared to control hydrogels without any adverse effect on reconstructed human epidermis samples in an in vitro skin irritation test system. From these data, we conclude that polyP-containing alginate/oxidized-alginate-gelatin hydrogels may provide a suitable regeneratively active matrix for wound healing for potential in vivo applications.